HUBUNGAN PENGETAHUAN DAN SIKAP REMAJA PUTRI DENGAN UPAYA PENANGANAN DISMENOREA DI SMA NEGERI 1 NAMORAMBE KAB. DELI SERDANG TAHUN 2019 - Erlina Hayati; Husna Sari (JURNAL ILMIAH DHDT - KEBIDANAN, 2019)
In Indonesia the incidence of primary type of dysmenorrhoea is around 54.89% while the rest are patients with secondary dysmenorrhoea. Dysmenorrhea occurs in teenage girl with a prevalence ranging from 43% to 93%, of which around 74-80% of teenage girl experience mild dysmenorrhea, while the incidence of endometriosis in teenage girl with pelvic pain is estimated at 25-38%, whereas in teenage girl who do not respond positively to treatment for menstrual pain, endometriosis is found in 67% of cases in laparoscopy. Dismenorrhea is an imbalance of the hormone progesterone in the blood resulting in pain, psychological factors play a role in the occurrence of dysmenorrhea in some women. Knowledge of dysmenorrhea is very influential on attitudes in dealing with dysmenorrhea. The attitude shown by young women is seen from how much knowledge teenage girl have. The research design used was descriptive analytic with cross sectional design. The studies sample was a 76 students of with dysmenorrhea 11th class teenage girl there were 76 people with dysmenorrhoea. The sampling technique is purposive sampling.Data were analyzed by Chi Square test. The results showed that the value of knowledge with efforts to treat dysmenorrhea was significant and the attitude value with efforts to treat dysmenorrhea was significant. It is expected that young women can increase their knowledge about reproductive health, especially the problem of dysmenorrhoea and efforts to handle it from reliable sources such as parents, health workers, teachers or reading books about women's reproductive health.